Mechanism of antibacterial resistance, strategies and next-generation antimicrobials to contain antimicrobial resistance: a review - Belay, Wubetu Yihunie; Getachew, Melese; Tegegne, Bantayehu Addis; Teffera, Zigale Hibstu; Dagne, Abebe; Zeleke, Tirsit Ketsela; Abebe, Rahel Belete; Gedif, Abebaw Abie; Fenta, Abebe; Yirdaw, Getasew; Tilahun, Adane; Aschale, Yibeltal (Frontiers in Pharmacology, 2024)
Antibacterial drug resistance poses a significant challenge to modern healthcare systems, threatening our ability to effectively treat bacterial infections. This review aims to provide a comprehensive overview of the types and mechanisms of antibacterial drug resistance. To achieve this aim, a thorough literature search was conducted to identify key studies and reviews on antibacterial resistance mechanisms. In this review, types of resistance and major mechanisms of antibacterial resistance with examples including target site modifications, decreased influx, increased efflux pumps, and enzymatic inactivation of antibacterials has been discussed. Moreover, biofilm formation, and horizontal gene transfer methods has also been included. Furthermore, measures (interventions) taken to control antimicrobial resistance and next-generation antimicrobials have been discussed in detail. Overall, this review provides valuable insights into the diverse mechanisms employed by bacteria to resist the effects of antibacterial drugs, with the aim of informing future research and guiding antimicrobial stewardship efforts.